PENERAPAN MODEL PBL DENGAN PENDEKATAN TaRL UNTUK MENINGKATKAN HASIL BELAJAR DAN PARTISIPASI PESERTA DIDIK - Ilmiah; Lady Agustina; Niswati Amin (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2025)
This study aims to improve the mathematics learning outcomes of eleventh-grade students on matrices through the application of the Problem-Based Learning model with the Teaching at the Right Level approach. The method used was Classroom Action Research, which was implemented in two cycles. Each cycle included planning, implementation, observation, and reflection. The results showed that in cycle 1, the average student score was 72.4, with a learning completion rate of 53.3%, which did not meet the Minimum Completion Criteria. The main obstacles faced were the imbalance of roles within the group, the lack of participation of low-ability students, and weak mentoring strategies. In cycle 2, after improvements were made through the provision of scaffolding, more structured group management, and task differentiation in the Student Worksheet, there was an increase in the average score to 81.2 with a learning completion rate of 86.7%. In addition, the classroom atmosphere became more collaborative and inclusive, and there was an increase in student confidence and involvement in the learning process. This integration concept can be tested on other materials to determine its effectiveness